Fluorescent Fluid in 3D‐Printed Microreactors for the Acceleration of Photocatalytic Reactions. Issue 13 (26th April 2019) - Zhang, Lijing; Zhu, Zhigang; Liu, Bofan; Li, Chong; Yu, Yongxian; Tao, Shengyang; Li, Tingju
Abstract: The photochemical microreactor has been a burgeoning field with important application in promoting photocatalytic reactions. The integration of light‐converting media and microflow chemistry renders new opportunity for efficient utilization of light and high conversion rate. However, the flexibility of emission light wavelength regulation and the universality of the microreactor remain significant problems to be solved. Here, a photochemical microreactor filled with fluorescent fluid is fabricated by a 3D printing technique. The light‐converting medium in the fluorescent fluid is used to collect and convert light, and then delivers light energy to the embedded continuous‐flow reaction channels to promote the chemical reaction process. With the merits of flowability, different light‐converting media can be replaced, making it a general tool for photocatalytic reactions in rapid screening, parameters optimization, and kinetic mechanism research. Abstract : A general‐used photochemical microreactor with a light channel and reaction channel is fabricated by 3D printing. The fluorescent fluid in light channel harvests and converts light to a narrow wavelength region and delivers light to the embedded reaction channel where photochemical reactions are accelerated. The flowability of the fluid enables flexible replacement of light‐converting media and reuse of the reactor.